Improving Management of Chronic Diseases by Generalist Practitioner - Jaffiol, Claude (Integrative Journal of Medical Sciences, 2017)
Chronic diseases lead to most deaths and health expenses in developed countries. Early diagnosis prevents these diseases from complications and decreases their cost. General practitioners seem to be the most available physicians to assume the health path of such patients. However several factors may affect their efficacy: the dramatic decrease of French practitioners since several years, the lack of adequate formation and medical time whereas two factors may affect the quality of therapeutic control during the follow up: poor compliance in drug use by the patient and clinical inertia by the general practitioner, both leading to reduced efficiency of therapy, increased complications and health expenses. Therapeutic education of the patients is the best response to improve the management of chronic diseases. However, most practitioners are unable to assume all the steps of health’s path including early diagnosis, prevention of chronic diseases, control, and therapeutic education. The reasons are the lack of formation, lack of time, and financial difficulties. To improve this situation we suggest: 1- to include psychological, social, and therapeutic education in the course of medical studies with a practical formation in urban and rural areas with particular attention for deprived populations. 2-to develop therapeutic education and the use of e-health for general practitioners. 3- to improve the links between private and hospital practices. 4- to increase the number of medical centers including medical and paramedical practitioners participating in a global health network coordinated by the general practitioner.